Upaya Pemulihan Ekonomi Pasca Covid dari Berbagai Sektor - Nurpan, Puteri Zaura Aprilia; Salahudin, Salahudin; Syamsulrizal, Syamsulrizal; Prinanda, Devita (Jurnal Samudra Ekonomi dan Bisnis, 2024)
Post-Covid-19 economic recovery is important for a country or region, including Grobogan Regency as a region in Central Java, Indonesia. The aim of the research is to determine economic recovery efforts in Grobogan Regency after Covid-19 in various sectors. This qualitative research collected data through interviews, documentation and observations conducted in January-February 2023. The results of data analysis found that economic recovery efforts in Grobogan Regency were carried out by providing various assistance to the community such as PKH, PIP, KIP, BLT programs, capital for MSMEs, interest on business loans at banks is smaller compared to the year before Covid-19, conducting various training for MSMEs and so on. It is hoped that these efforts will be able to improve the economy of regional communities after the Covid-19 pandemic.